FENOMENA SELF-HEALING TERHADAP KRISIS SPIRITUALITAS GENERASI Z DI STIT DARUL ULUM KOTABARU - Muhammad Yamani Ghani; Aisyah; Rizky Aisya Nor Shela; Sapna Agustina; Wahjurni Maliya (STIT DARUL ULUM KOTABARU, 2026)
The phenomenon of mental health among younger demographics has emerged as a pervasive global concern that has seen significant escalation over the past decade. Empirical data from various international studies indicates that Generation Z experiences higher levels of psychological distress compared to previous generations, driven by their exposure to digital media, societal expectations, and uncertainty about the future. This study examines the phenomenon of self-healing as a response to the spiritual crisis among Generation Z, specifically students at STIT Darul Ulum Kotabaru. Using a qualitative approach, this study analyzes the students' self-healing practices, as well as the relationship and meaning of self-healing within the context of the spiritual crisis. The results indicate that self-healing not only functions as an effort to relieve psychological distress but also as a means of self-reflection and strengthening spirituality through religious activities. These findings strengthen the link between psychological coping and spiritual well-being and provide recommendations for the development of spirituality-based student mentoring programs. This research contributes to a holistic understanding of the self-healing phenomenon in the digital era.